Exploration and Petrogenesis of Corundum-Bearing Pegmatites: A Case Study in Migif-Hafafit Area, Egypt - Khaleal, Farrage M.; Saleh, Gehad M.; Lasheen, El Saeed R.; Alzahrani, Abdullah M.; Kamh, Samir Z. (Frontiers in Earth Science, 2022)
A net of pegmatite veins crosscut gneiss and dismembered ophiolitic ultramafic rocks are abundant in the Migif-Hafafit culmination area, South Eastern Desert, Egypt. Some of these pegmatites are corundum-bearing. Corundum-bearing pegmatites are studied in eight localities around the Migif-Hafafit complex. The present study aims to integrate field investigation, whole rock and corundum chemistry, remote sensing studies, and the conventional methods to detect the corundum-bearing pegmatites, which led to finding out the genesis of the corundum mineralization. In addition, the tectonic regime has been detected using bulk rock geochemistry. False-color composite (FCCs), band ratio (BR), principal component analysis (PCA), minimum noise fraction (MNF), decorrelation stretch (DS), and the constrained energy minimization (CEM) image processing algorithms were proposed and applied on Landsat-8 OLI, and Sentinel-2A data to discriminate the exposed lithological units and to detect the corundum-bearing pegmatites in the study area. These detected pegmatites are structurally controlled following the NW-SE direction. The ultramafic rocks are the host of six areas and the gneisses are the host rocks of the two others. Gneisses and pegmatites are characterized by a steep slope of LREEs relative to HREEs with week Eu negative anomaly. The studied pegmatites have both plumasite and marundite. On the other hand, the studied corundum has Al2O3 content up to 99.72 wt% in pegmatite-gneiss and up to 100 wt.% in pegmatite-ultramafics. Corundum is ascribed to metamorphic/metasomatic type according to its chromosphere. Desilication in pegmatites led to the excess of alumina content in the residual melt producing corundum mineralization.